Copper promoted catalytic cleavage of esters under nearly neutral conditions in the presence of NaN3. Issue 21 (20th May 2015) - Sun, Hong-bin; Ai, Yongjian; Ren, Shanshan; Li, Yuanyuan; Li, Dong
Graphical abstract: Abstract: The cleavage of carboxylic acid esters is promoted by malachite in the presence of NaN3 under nearly neutral conditions. In methanol, the aliphatic alcohol esters are converted to methyl esters and corresponding alcohols in good to excellent yields, while the cleavage of phenolic esters gives phenols in quantitative yields. In most cases, the reaction conditions are quite mild so this methodology is efficient for the removal of the acyl-protecting group from the protected hydroxy functional groups. The possible catalytic mechanism is discussed according to some experimental features.